2018
DOI: 10.1002/jum.14679
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Measurement of Sciatic Nerve Stiffness in Patients With Chronic Low Back Related Leg Pain Using Shear Wave Elastography

Abstract: People with chronic low back-related leg pain have interlimb differences in sciatic nerve stiffness, as measured by a safe and noninvasive method: shear wave elastography. The changes found may be related to alterations in nerve mechanical properties, which should be confirmed by future investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 21 publications
1
43
0
Order By: Relevance
“…There is a growing body of evidence of in-vivo studies supporting that mechanical properties of human peripheral nerves are altered in various peripheral neuropathies, such as those associated with nerve compression [60], metabolic syndrome [61], and radiculopathies [62][63][64]. Interestingly, a preliminary study reported that a 3-min slump (static) stretch resulted in an immediate decrease in sciatic nerve stiffness in people with unilateral sciatica [65].…”
Section: Evidence From Human Trialsmentioning
confidence: 99%
“…There is a growing body of evidence of in-vivo studies supporting that mechanical properties of human peripheral nerves are altered in various peripheral neuropathies, such as those associated with nerve compression [60], metabolic syndrome [61], and radiculopathies [62][63][64]. Interestingly, a preliminary study reported that a 3-min slump (static) stretch resulted in an immediate decrease in sciatic nerve stiffness in people with unilateral sciatica [65].…”
Section: Evidence From Human Trialsmentioning
confidence: 99%
“…The shear wave features were presented in different conditions and diseases, respectively in healthy patients. Neto et al [26] presented higher sciatic nerve stiffness compared to the unaffected limb (8.2 to 16.2m/sec and 9 to 13.6m/sec, P=.05) in patients with chronic low back leg pain. The resistance (shear-wave technique) in dynamic and unresisting knee extension was observed by Ellis [17].…”
Section: Resultsmentioning
confidence: 92%
“…However, there is limited understanding of the effects of nerve tension on SW velocity because this has never been studied in two nerves of the same limb. Previous reports have only individually analyzed the median, tibial, and sciatic nerves. In addition, the interactive effects of extrinsic and intrinsic factors, such as nerve tension and structure/composition, on SW velocity remain to be determined.…”
Section: Introductionmentioning
confidence: 99%